Prevalence of Plasmid-Mediated Quinolone Resistance Genes among Ciprofloxacin-Nonsusceptible Escherichia coli and Klebsiella pneumoniae Isolated from Blood Cultures in Korea - Hee Young Yang; You Sun Nam; Hee Joo Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVES:To analyze the prevalence of plasmid-mediated quinolone resistance (PMQR) determinants in ciprofloxacin-nonsusceptible Escherichia coli and Klebsiella pneumoniae isolated from patients at a tertiary care hospital in Korea.